New Qualitative Methods for Assessing the “Fluid” in the Retina in Age-Related Macular Degeneration - M. V. Budzinskaya; A. A. Plyukhova (Oftalʹmologiâ)
Age-related macular degeneration (AMD) is a chronic disease of the central retina and one of the main causes of blindness in patients over 60 years of age in industrialized countries. Currently, anti-vascular endothelial growth factor therapy (anti-VEGF therapy) has become the standard of neovascular AMD treatment, leading to the prevention of progressive vision loss in more than 90 % of treated patients during a two-year follow-up period. In the modern world there are transition from quantitative assessment of “fluid” according to optical coherence tomography (OCT) — the thickness of the central retinal zone, to qualitative — the presence of IRF, SRF, fluid under RPE. The data obtained by Zinkernagel have shown that, despite good functional results (an increase in visual acuity), the administration of the drug once every 2 months leads not only to fluctuations in IRF and SRF, but also to serous PED [4]. The existing qualitative and quantitative analysis is not perfect. Fluctuation is a new qualitative marker of the study of disease activity, it is defined as the sum of all types of fluid (IRF + SRF + fluid under RPE) in a certain time interval (with monthly measurement of the indicator). The fluctuation index was determined from the cumulative change in the thickness of the retina in the fovea over time [6]. Thus, the fluid is considered as a key morphological criterion for the activity of nVMD and an indication for (initiation or continuation) of antiangiogenic therapy. At the same time, there is evidence that a lower level of each type of fluid (IRF, SRF, fluid under RPE) is associated with better BCVA results against the background of anti-VEGF therapy [17]. The stability of retinal thickness during anti-VEGF therapy is no less important parameter than the statement of fluid resolution at a certain time, and it appears that better control of the central retinal thickness was associated with higher overall NEI VFQ-25 scores and individual scales reflecting important daily activities of the patient [16].